ChemInform Abstract: Elements of Regiocontrol in the Direct Heteroarylation of Indoles/Pyrroles: Synthesis of Bi‐ and Fused Polycyclic Heteroarenes by Twofold or Tandem Fourfold C—H Activation. Issue 20 (25th April 2013) - Wang, Zhen; Song, Feijie; Zhao, Yinsong; Huang, Yumin; Yang, Lei; Zhao, Dongbing; Lan, Jingbo; You, Jingsong
Abstract The first palladium‐catalyzed cascade reaction involving the cleavage of four C—H bonds and the formation of two C—C bonds is presented [viz.